Whistleblowing nation : the history of national security disclosures and the cult of state secrecy - Mistry, Kaeten, 1980-; Gurman, Hannah (Columbia University Press, 2020)
"The twenty-first century witnessed a new age of whistleblowing in the United States. Disclosures by Chelsea Manning, Edward Snowden, and others have stoked heated public debates about the ethics of exposing institutional secrets, with roots in a longer history of state insiders revealing privileged information. Bringing together contributors from a range of disciplines to consider political, legal, and cultural dimensions, Whistleblowing Nation is a pathbreaking history of national security disclosures and state secrecy from World War I to the present. The contributors explore the complex politics, motives, and ideologies behind the revelation of state secrets that threaten the status quo, challenging reductive characterizations of whistleblowers as heroes or traitors. They examine the dynamics of state retaliation, political backlash, and civic contests over the legitimacy and significance of the exposure and the whistleblower. The volume considers the growing power of the executive branch and its consequences for First Amendment rights, the protection and prosecution of whistleblowers, and the rise of vast classification and censorship regimes within the national-security state. Featuring analyses from leading historians, literary scholars, legal experts, and political scientists, Whistleblowing Nation sheds new light on the tension of secrecy and transparency, security and civil liberties, and the politics of truth and falsehood"--